Cortisol, dehydroepiandrosterone sulfate, fatty acids, and their relation in recurrent depression. (February 2019) - ter Horst, D.M.; Schene, A.H.; Figueroa, C.A.; Assies, J.; Lok, A.; Bockting, C.L.H.; Ruhé, H.G.; Mocking, R.J.T.
Highlights: Remitted unmedicated recurrent MDD patients had higher cortisol awakening responses. In patients versus controls, awakening DHEAS was inversely related with fatty acids. Findings corroborate persistent changes in HPA axis and metabolism in recurrent MDD. Future research could aid in the development of recurrence-vulnerability biomarkers. Abstract: Background: Alterations in hypothalamic–pituitary–adrenal (HPA)-axis activity, fatty acid metabolism, and their relation have been associated with (recurrent) major depressive disorder (MDD), although conflicting findings exist. Aims: To determine whether alterations in HPA-axis activity and fatty acids in recurrent MDD remain during remission (i.e. reflect a potential trait factor). Furthermore, to test the association between HPA-axis activity and fatty acids in patients versus controls. Methods: We cross-sectionally compared 73 remitted unmedicated recurrent MDD patients with 46 matched never-depressed controls. Measurements included salivary cortisol and dehydroepiandrosterone sulfate (DHEAS) (awakening, evening, and after sad mood induction) and erythrocyte fatty acid parameters: (I) three main fatty acids [omega-3 docosahexaenoic acid (DHA), and the omega-3 eicosapentaenoic acid/omega-6 arachidonic acid (EPA/AA)-ratio], and (II) structural fatty acid indices [chain length, unsaturation and peroxidation]. Results: Patients showed higher cortisol awakening responses ( p  = 0.006) and lower evening cortisol/DHEAS ratios ( p  = 0.044) compared to matched controls. Fatty acids did not differ between patients and controls, but HPA-axis indicators were significantly associated with fatty acid parameters in both groups (0.001 ≤  p  ≤ 0.043). Patients and controls significantly differed in the relations between awakening DHEAS or cortisol/DHEAS ratios and fatty acid parameters, including unsaturation and peroxidation indices (0.001≤  p  ≤ 0.034). Significance remained after correction for confounders. Conclusions: Our results further support alterations in HPA-axis activity, i.e. a lower baseline, but higher responsiveness of awakening cortisol, in remitted medication-free recurrent MDD patients. Furthermore, the relationship between HPA-axis and fatty acids showed significant differences in recurrent MDD patients versus controls. Prospective research is needed to determine the predictive value of this relationship for MDD recurrence.